Analysis of the Selection and Employment Model of College Counselors from the Perspective of Human Resources Management - Liu, Zhencong; Diao, Huiying (Journal of Education and Educational Technologies, 2023)
In the context of the continuous deepening of the reform of public institutions by the country, universities, as special public institutions, need to continuously explore and try reform paths that are in line with their own development. The enterprise human resource management model serves as a means to optimize and adjust the internal personnel structure and better achieve human resource allocation, providing reference and reference for the selection and employment of college counselors. Therefore, in order to further improve the quality of college counselor selection, it is necessary to apply advanced concepts of human resource management, clarify counselor selection standards, and better complete the construction of the college counselor team. This article analyzes the current situation of college counselor selection and proposes innovative selection models to address the main problems, in order to promote the improvement of the quality and ability of college counselors.